The Hesitation of Students in Speaking English at the English Education Study Program Universitas Islam Ahmad Dahlan Sinjai - Karina, Siti; Harmilawati; Indirwan (JLE: Journal of Literate of English Education Study Program, 2023)
Speaking is not only conveying certain meanings but sometimes producing utterances has other meanings, speaking often suddenly changes thoughts, this then results in non-fluency in English. The purpose of this study was to find out the types of hesitation in speaking English in the English language education study program and to find out the factors of students' hesitation in speaking English in the English language education study program Classes of Islamic University of Ahmad Dahlan Sinjai. The type of research used in this research is phenomenological research, qualitative research pays attention to qualitative phenomena related to quality or diversity. Individual beliefs, experiences, and systems of meaning are of particular concern to qualitative researchers. The results of this study found that the most common doubts were fillers that were not lexical such as uhh, err, ee, aah, umm, and ehmm. The slightest hesitation is that a false start must be traced back. And also, there are nine types of doubt that occur viz 1).Silent Pause 2).Filler, 3).Repeat, 4).False Start, (Unrestricted), 5). False Start (Retraced) 6).Corrections, 7). nterjection, 8). Stutters, and 9). Slip of tongue. Based on previous observations, it can be concluded that all students of Islamic University of Ahmad Dahlan Sinjai who are the object of research show hesitation when speaking English.